2014
DOI: 10.1111/desc.12189
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive mechanisms of learning to read: print tuning in beginning readers related to word‐reading fluency and semantics but not phonology

Abstract: During reading acquisition children learn to recognize orthographic stimuli and link them to phonology and semantics. The present study investigated neurocognitive processes of learning to read after one year of schooling. We aimed to elucidate the cognitive processes underlying neural tuning for print that has been shown to play an important role for reading and dyslexia. A 128-channel EEG was recorded while 68 (Swiss-)German monolingual first grade children (mean age: 7.6) performed a one-back task with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
89
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(111 citation statements)
references
References 49 publications
15
89
5
1
Order By: Relevance
“…In addition, similarly to previous studies (e.g., Maurer et al, 2005Maurer et al, , 2011, pseudowords and symbolsequences evoked responses already in the earlier P1 component, reflecting that letter-specific processing in adults is under way as early as 80-120 ms. Taken together, the observed ERP activity is compatible with the idea that reading acquisition, and skilled processing of letters, drives the emergence of a perceptual mechanism specifically attuned to the properties of the orthographic code, signaled by the P1/N1 electrophysiological response Maurer et al, 2005Maurer et al, , 2006McCandliss et al, 2003). We note that in earlier ERP studies using false-font instead to better control for low-level visual differences with letters, print tuning effects were still robust (Eberhard-Moscicka et al, 2014), suggesting that the effects shown in studies using symbol strings are not due to low-level differences.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, similarly to previous studies (e.g., Maurer et al, 2005Maurer et al, , 2011, pseudowords and symbolsequences evoked responses already in the earlier P1 component, reflecting that letter-specific processing in adults is under way as early as 80-120 ms. Taken together, the observed ERP activity is compatible with the idea that reading acquisition, and skilled processing of letters, drives the emergence of a perceptual mechanism specifically attuned to the properties of the orthographic code, signaled by the P1/N1 electrophysiological response Maurer et al, 2005Maurer et al, , 2006McCandliss et al, 2003). We note that in earlier ERP studies using false-font instead to better control for low-level visual differences with letters, print tuning effects were still robust (Eberhard-Moscicka et al, 2014), suggesting that the effects shown in studies using symbol strings are not due to low-level differences.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, N1 difference in the ERPs between words and false-font strings was found by the end of the first grade, both at the group and individual response level (Eberhard-Moscicka, http://dx.doi.org/10.1016/j.bandl.2014.11.007 0093-934X/Ó 2014 Elsevier Inc. All rights reserved. Jost, Raith, & Maurer, 2014). Moreover, another result supporting the claim that the N1 reflects a specific brain training effect comes from studies with populations of different reading expertise: the N1 response is attenuated in groups lacking reading expertise such as dyslexic children (Araújo, Faísca, Bramão, Petersson, & Reis, 2012;Hasko, Groth, Bruder, Bartling, & Schulte-Körne, 2013; and adults Mahé, Bonnefond, Gavens, Dufour, & Doignon-Camus, 2012).…”
Section: Introductionmentioning
confidence: 86%
“…These findings agree with the left posterior hemispheric dominance in processing letter strings, as found in adults with a variety of approaches (11,28,29) including the paradigm used here (24). However, it challenges the view that left-hemispheric specialization emerges relatively late in natural settings, that is, after at least 1 y of formal reading instruction (13,14). At the theoretical level, this finding indicates that minimal knowledge of grapheme-phoneme association is sufficient to induce neural changes, suggesting rapid plasticity in establishing connections between posterior visual and anterior phonological regions during development.…”
Section: Discussionsupporting
confidence: 83%
“…It has been found that Pinyin exhibited the similar mechanism of the orthographic-to-phonological mapping as in alphabetic writing systems (Wang et al, 2005). The orthographic-to-phonological mapping is a key element of reading fluency (Norton and Wolf, 2012; Eberhard-Moscicka et al, 2014; Hakvoort et al, 2015). The visual rapid temporal processing was hypothesized to be crucially involved in the mapping between spelling and sound as it requires the visual engagement and disengagement of each sub-lexical unit (Gori et al, 2014; Ruffino et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As the result, the automatization of the orthographic-to-phonological mapping would be achieved earlier in languages with shallow orthography (Wolf and Katzir-Cohen, 2001; Xue et al, 2013). The efficient orthographic-to-phonological mapping is critical for reading fluency (especially for oral reading fluency, Norton and Wolf, 2012; Eberhard-Moscicka et al, 2014; Hakvoort et al, 2015), and it has been suggested that the visual rapid temporal processing played a role in the mapping between spelling and sound which required the visually serial engagement and disengagement from each sub-lexical unit (Gori et al, 2014; Ruffino et al, 2014). Accordingly, due to its’ consistent grapheme-phoneme correspondence in shallow languages, the skilled readers may not show a close relationship between the (oral) reading fluency and visual rapid temporal processing in shallow orthographies.…”
Section: Introductionmentioning
confidence: 99%